The prevalence and risk factors of chronic kidney disease among type 2 diabetes mellitus follow-up patients at Debre Berhan Referral Hospital, Central Ethiopia - Mulu, Getaneh Baye; Kebede, Worku Misganew; Tarekegn, Fetene Nigussie; Engida, Abayneh Shewangzaw; Tiruye, Migbaru Endawoke; Menalu, Mulat Mossie; Mossie, Yalew; Teshome, Wubshet; Atinafu, Bantalem Tilaye (Journal of Clinical Nephrology, 2023)
Background: Chronic kidney disease is a progressive loss in renal function that is more accepted as global public health importance and its magnitude is overgrowing in the least developed countries like Ethiopia. No data was found in Debre Birhan Central Ethiopia on the magnitude of chronic kidney disease among type 2 diabetes patients. Methods: Institution-based cross-sectional study was conducted among 327 at Debre Berhan Referral Hospital from March to June 2019 in Adult (≥ 18 years) type 2 diabetes follow-up patients who volunteered to give informed written consent were included in the study. Systematic random sampling was used. Data were collected by interviews using structured and pre-tested questionnaires. Descriptive statistics of the continuous and categorical variables were done. The bi-variable and multivariable logistic regression was done to show the net effect of explanatory variables on chronic renal disease. Results: A total of 327 study participants were involved in the final analysis. The Prevalence of CKD among type 2 diabetic patients was 15.9%. A significant association was found with age > 60 years [AOR 3.5 (95% CI 1.8-6.8)], alcoholic patients [AOR 2.4 (95% CI 1.2-5.1)], glycated hemoglobin levels above 7% [AOR 2.5 (95 CI 1.5-4.1)], higher level of LDL greater than 100 g/dl [AOR 2.7 (95% CI 1.9-4)] and lower level of HDL [AOR 2.9 (95% CI 1.4-6)]. Conclusion: The magnitude of chronic kidney disease among type 2 diabetic follow-up patients was 15.9%. Estimated GFR should be determined for diabetic patients at regular intervals of time for earlier diagnosis of chronic kidney disease.